ULTRASTRUCTURAL STUDY ON SPERMATOGENESIS IN RUMEN AMPHISTOME ORTHOCOELIUM SCOLIOCOELIUM (TREMATODA: DIGENEA), A PARASITE OF BUBALUS BUBALIS IN UDAIPUR - GAYATRI SWARNAKAR (The Bioscan, 2010)
Spermatogenesis in rumen amphistome species Orthocoelium scoliocoelium (Trematoda: Digenea, Paramphistomidae) a parasite of Bubalis bubalis has been examined by transmission electron microscopy. Observations demonstrated that the each testis is covered by tunica with fibrous connective tissues. Below the tunica different stages of spermatogonia, spermatocytes, spermatid cells and spermatozoa were observed. The spermatozoon of O. scoliocoelium are elongate, similar to the pattern described in other digenea, showing nuclei, mitochondria and two axonemes with the 9+1 configuration. On the basis of present investigations, it may be concluded that the ultrastructure of spermatogenesis in amphistome O. scoliocoelium basically follows the common digenean plan.